2012
DOI: 10.2165/11595460-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Endurance Exercise Intensity Determination in the Rehabilitation of Coronary Artery Disease Patients

Abstract: In the care of coronary artery disease (CAD) patients, the benefits of exercise therapy are generally established. Even though the selected endurance exercise intensity might affect medical safety, therapy adherence and effectiveness in the rehabilitation of CAD patients in how to determine endurance exercise intensity properly remains difficult. The aim of this review is to describe the available methods for endurance exercise intensity determination in the rehabilitation of CAD patients, accompanied with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
33
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 79 publications
0
33
0
1
Order By: Relevance
“…An important requirement for ECR programs to be safe and effective is an exact determination of exercise intensity using parameters derived from a symptom-limited exercise test [8]. From a safety perspective, exercise intensity should not be too high as it has been postulated that strenuous exercise increases platelet activation [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…An important requirement for ECR programs to be safe and effective is an exact determination of exercise intensity using parameters derived from a symptom-limited exercise test [8]. From a safety perspective, exercise intensity should not be too high as it has been postulated that strenuous exercise increases platelet activation [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The trainings are done at intensities that range from 40 to 85% of the HRR 2,14,16,17 as determined by the formula proposed by Karvonen et al 18 The HRR is an important physiological variable to quantify the maximum effort during training, and is also an important indicator used to prescribe training intensities of aerobic exercise programs -in addition, it presents a good correlation with the tests done on stationary bicycles. 19,20 The importance of and the training parameters for hemiparetics are well established, however there is no clear description as to the speed to be used to begin treadmill training in a clinical physiotherapeutic practice.…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of gas exchange analyzers, VO 2 at VT can be determined by invasive lactate blood samples [17,18]. In their review, Hansen et al [22] underlined that VT 1 and Anaerobic Threshold (AT) are used interchangeably in the literature. They nevertheless reported a wide range (from 58 to 75 % of VO 2 peak) in AT determination and so a significant difference in heart rate value according to the method used [22].…”
Section: Introductionmentioning
confidence: 99%
“…In their review, Hansen et al [22] underlined that VT 1 and Anaerobic Threshold (AT) are used interchangeably in the literature. They nevertheless reported a wide range (from 58 to 75 % of VO 2 peak) in AT determination and so a significant difference in heart rate value according to the method used [22]. Zanettini et al [23] also reported that Self-regulation of exercise intensity based on BORG score was associated to higher heart rate values than VT 1 workload.…”
Section: Introductionmentioning
confidence: 99%